Prevalence and laboratory analysis of malaria and dengue co-infection: a systematic review and meta-analysis - Manas Kotepui; Kwuntida Uthaisar Kotepui (BMC, 2019)
Abstract Background A clear understanding of the epidemiology of malaria and dengue co-infection is essential for informed decisions on appropriate control strategies for dengue and malaria. This systematic review synthesized evidence on the relationship of malaria and dengue co-infection and related it to alterations in platelet, hemoglobin, hematocrit, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) levels when compared to malaria mono-infection. Methods A systematic review in accordance with PRISMA guidelines was conducted. All published articles available in PubMed and Web of Science (ISI) databases before October 21, 2017 were recruited. All epidemiological studies except case reports on the prevalence or incidence of malaria and dengue co-infection among patients visiting hospitals with febrile illness were included. Studies that involved conference abstracts, protocols, systematic reviews, only mono-dengue or mono-malaria infections, and only animal or in vitro studies were excluded after screening the titles, abstracts, and body texts. Studies were additionally excluded after full text review when they lacked epidemiologic data on malaria and dengue co-infection. Two reviewers independently screened, reviewed, and assessed all the studies. Cochrane Q (Chi-square) and Moran's I2 were used to assess heterogeneity, and the funnel plot was used to examine publication bias. The summary odds ratio (OR) and 95% confidence intervals (CI) were estimated using a fixed-effects model. Thirteen cross-sectional and two retrospective studies were eligible to be included in the systematic review and meta-analysis. Results Out of the 2269 citations screened, 15 articles were eligible to be included in the systematic review and meta-analysis. The 15 studies involved 13,798 (10,373 cases with malaria and 3425 with dengue) patients in 9 countries. Thirteen studies compared the incidence and odds of Plasmodium sp. infection, five studies compared the odds of mean platelet, three studies compared Plasmodium parasite density, and four studies compared the odds of hemoglobin, hematocrit, AST, and ALT levels among co-infected groups and single-malaria-infected groups. Conclusions This study showed that dengue and malaria co-infection was associated with decreased odds of malaria infection, malaria parasitemia, AST, and ALT levels when compared to malaria mono-infection. However, malaria and dengue co-infection was associated with increased odds of platelet and hemoglobin levels when compared to malaria mono-infection.